Analisis Tingkat Pengetahuan Pekerja Terhadap Keselamatan Dan Kesehatan Kerja (K3) Pada Proyek Pembangunan Rumah Sakit Mata Makassar - Yamsal; Josefine Ernestine Latupeirissa; Herby Calvin Pascal Tiyow (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
In a development project, the risk of work accidents is very high. The cause is the lack of knowledge of employees or workers about occupational safety and health protection. Thus, an analysis was carried out on the level of knowledge of workers on Occupational Safety and Health (K3) in the Makassar Eye Hospital Construction Project. The research will be conducted by means of direct interviews and field surveys. The interviews targeted 20 handymen and 4 foremen who were working on the Makassar Eye Hospital construction project. The questionnaire contains general information about the employee and the employee's knowledge of K3. Based on the results of the research obtained, Makassar eye hospital project workers still do not understand employee safety due to several factors, among others, low worker training, lack of work experience and the number of workers who have never participated in on the job training.